Din, Müzik ve Kimlik Bağlamında Türkiye'de İslami Popüler Müzik / Islamic Popular Music in Turkey within the Context of Religion, Music and Identity - Yenen, İbrahim (Journal of History Culture and Art Research, 2016)
Islamic Popular Music in Turkey within the Context of Religion, Music and Identity Abstract This article, by examining the culture of Islamic Popular Music in Turkey, examines the role of this culture in forming and expressing of Islamic identity. The aim of this article is to point out how Islamic identity is expressed and transferred by means of popular music and what kind of changes this identity formed by means of Islamic music has experienced from 1990s to 2000s. This study has made analysis in the light of the following hypothesis “Islamic Popular Music is one of the important cultural components in comprehending the Islamic understanding of the period.” The samples of the style of Islamic Popular Music between 1990-2000 were named as “Islamic Protest Music”. The most significant characteristic of Islamic Protest Music in 1990s is that the message contents rely on the distinction of “we and others”. In 2000s, Islamic Popular Music has turned into Islamic popular music which is away from giving a message through its melody, rhytm and instruments but carries commercial worries in accordance with the concerns of music industry. Din, Müzik ve Kimlik Bağlamında Türkiye'de İslami Popüler Müzik Öz Bu makale, Türkiye’de İslami Popüler Müzik kültürünü inceleyerek bu kültürün İslami kimliğin oluşması ve ifade edilmesi üzerinde nasıl bir etkisi olduğunu incelemektedir. Makalenin amacı, İslami kimliğin popüler müzik aracılığıyla nasıl ifade edildiği, aktarıldığı,ve ayrıca İslami müzik aracılığıyla oluşturulan bu kimliğin 90’lı yıllardan 2000’li yıllara nasıl bir değişim geçirdiğini göstermektir. Çalışmada “Dönemin İslami anlayışının kavranabilmesinde İslami popüler müzikler önemli kültürel öğelerden birisidir” varsayımından hareketle çözümlemeler yapılmıştır. İslami popüler müzik tarzının 1990-2000 yılları arasındaki örnekleri, “İslami protest müzik” olarak isimlendirilmiştir. 90’lı yıllar İslami protest müziğin en belirgin özelliği, mesaj içeriklerinin “biz ve onlar” ayrımına dayalı olmasıdır. 2000’li yıllarla birlikte İslami popüler müzik, ezgi, ritim ve enstrümanlarıyla mesaj iletme amacından uzak, müzik piyasasının gereklerine uygun bir şekilde ticari kaygı öncelikli, İslami bir pop müzik türü haline gelmiştir.